Structure of Herbaceous Vegetation of Recovering Forest Stands in Koraput Region of Odisha, India - Pathak, Abhay K.; Misra, Malaya K. (Indian Forester, 2016)
The paper presents the assessment of the impact of local protection of degraded forest stands for 4, 6, 8, 10, 12 and 20 year periods in the Koraput region of Odisha, India on the structural characters of the herbaceous vegetation. The pooled number of all plant species in all the stands was 173 under 151 genera and 57 families. Total individuals of all herbaceous species recorded were 84, 62, 65, 66, 58, and 53 plants m-2 in 4, 6, 8, 10, 12 and 20 year stands, respectively. Herbaceous stand basal area was 3.4, 1.83, 1.83, 1.86, 1.62, and 1.45 cm2 m-2 in 4, 6, 8, 10, 12 and 20 year stands, respectively. Importance value index (IVI) revealed that Chrysopogon aciculatus, Desmodium triflorum, Vicoa indica, Capillipedium assimile, Jasminum arborescens and Ageratum conyzoidis predominated in 4, 6, 8, 10, 12 and 20 year stands, respectively. Dominance-diversity curve for the six herbaceous stands showed lognormal distribution. Shannon’s diversity index (H’) and Simpson’s dominance index (C) for the six herbaceous stands were almost same in all the six stands. The shift in dominance of herbaceous species with longer protection age suggests the initiation of stabilization process and establishment of shade tolerant species.